2016
DOI: 10.1152/jn.00565.2015
|View full text |Cite
|
Sign up to set email alerts
|

Increased intensity and reduced frequency of EMG signals from feline self-reinnervated ankle extensors during walking do not normalize excessive lengthening

Abstract: Pantall A, Hodson-Tole EF, Gregor RJ, Prilutsky BI. Increased intensity and reduced frequency of EMG signals from feline selfreinnervated ankle extensors during walking do not normalize excessive lengthening. J Neurophysiol 115: 2406 -2420, 2016. First published February 24, 2016 doi:10.1152/jn.00565.2015-Kinematics of cat level walking recover after elimination of length-dependent sensory feedback from the major ankle extensor muscles induced by self-reinnervation. Little is known, however, about changes in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 88 publications
1
13
0
Order By: Relevance
“…It is possible but less clear how preservation of intermuscular feedback could be directly responsible for such compensatory actions. During downslope walking, it has recently been reported that the mean myoelectric magnitude of the self-reinnervated SOL muscle (but not lateral G) was higher, 10 -12 wk after nerve repair, compared with before injury, but the ankle net joint moment was the same as control recordings (Pantall et al 2016). The finding of "normal" ankle net joint moment but exaggerated ankle yielding, despite the same or greater muscle activation, is best explained by a greater contribution of passive parallel elastic muscle components (i.e., ineffective muscle activation) that might stimulate Golgi tendon organs.…”
Section: Potential Role Of Preserved Intermuscular Length and Force Fmentioning
confidence: 87%
See 3 more Smart Citations
“…It is possible but less clear how preservation of intermuscular feedback could be directly responsible for such compensatory actions. During downslope walking, it has recently been reported that the mean myoelectric magnitude of the self-reinnervated SOL muscle (but not lateral G) was higher, 10 -12 wk after nerve repair, compared with before injury, but the ankle net joint moment was the same as control recordings (Pantall et al 2016). The finding of "normal" ankle net joint moment but exaggerated ankle yielding, despite the same or greater muscle activation, is best explained by a greater contribution of passive parallel elastic muscle components (i.e., ineffective muscle activation) that might stimulate Golgi tendon organs.…”
Section: Potential Role Of Preserved Intermuscular Length and Force Fmentioning
confidence: 87%
“…Table 1 are cat-identifier labels, based on which muscle nerves were cut and repaired, and subject characteristics. Signs of motor recovery identified by EMG begin around 4 wk after nerve cut and repair, and locomotor mechanics and EMG returns to presurgery levels during level and upslope walking within 10 -14 wk (Maas et al 2007;Pantall et al 2016). The data reported here were collected at a minimum of 19 wk after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative timing of motor activity onset may reveal dysfunction of sensorimotor integration. Spectral characteristics of the EMG signal may indicate altered motor unit recruitment strategies 22,23 and presence of fatigue 24 . Multi-muscle EMG analysis and intermuscular coherence may provide information about global control networks 25,26 .…”
Section: Introductionmentioning
confidence: 99%